Do magnification loupes affect the precision of cavity preparations made by undergraduates? A randomized crossover study - Florin Eggmann; Delia R. Irani; Patrizia A. Fehlbaum; Klaus W. Neuhaus (BMC, 2022)
Abstract Background Evidence on the effect of magnification devices on procedure quality in restorative dentistry is scant. This study therefore aimed to assess, under simulated clinical conditions, if magnification loupes affect the quality of preparations carried out by undergraduate dental students. Methods 59 undergraduate dental students underwent two visual acuity tests, based on which they were divided into a "low visual acuity group" (visus < 1) and a "good visual acuity group" (visus ≥ 1). In a randomized crossover experiment, participants performed a two-dimensional S and a three-dimensional O figure preparation with a dental handpiece on standardized acrylic blocs designed for preclinical restorative training. Each participant carried out the preparation tasks twice, once with magnification loupes (2.5×) and once without. Two blinded investigators independently evaluated parameters of preparation precision. Data were analyzed using Spearman rank correlation coefficients, intra-class correlation coefficients, and Wilcoxon rank-sum tests (α = 0.05). Results Participants from the "low visual acuity group" did not show a statistically significant improvement in accuracy when they used magnification loupes for the S figure preparation (p ≥ 0.0625). Participants from the "high visual acuity group" obtained a higher level of accuracy (p ≤ 0.0012) when they used magnification loupes for the S figure preparation. The use of magnification loupes had no statistically significant effect on the accuracy parameters of the O figure cavity preparations (p ≥ 0.1865). Participants with high visual acuity achieved only a marginally better accuracy than participants with a visus < 1. Conclusions This study suggests that loupes with 2.5× magnification increase the accuracy of two-dimensional preparations while they have no significant effect, favorable or otherwise, on the accuracy of complex, three-dimensional cavity preparations of untrained dental students.